Prostate Cancer Theranostics - An Overview - Abou, Diane; Benabdallah, Nadia; Jiang, Wen; Peng, Lu; Zhang, Hanwen; Villmer, Alexandria; Longtine, Mark S.; Thorek, Daniel L. J. (Frontiers in Oncology, 2020)
Metastatic prostate cancer is incurable, and novel methods to detect the disease earlier and to direct definitive treatment are needed. Molecularly specific tools to localize diagnostic and cytotoxic radionuclide payloads to cancer cells and the surrounding microenvironment are recognized as a critical component of new approaches to combat this disease. The implementation of theranostic approaches to characterize and personalize patient management is beginning to be realized for prostate cancer patients. This review article summarized clinically translated approaches to detect, characterize and treat disease in this rapidly expanding field.